A survey of the professional identity of clinical psychologists in South Africa - Deane, Tessa Anne (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
The mental health care needs of South Africa have shifted significantly in the postapartheid context of changing political and socioeconomic landscapes. However, the extent to which clinical psychologists' professional identity has responded accordingly has been unclear. By establishing the practice patterns and values that should be central to the profession according to the literature, and ascertaining the extent to which these are reflected among professionals at this time, this study facilitates a re-evaluation of the professional identity of clinical psychologists in South Africa. To this end, an online survey method was used to collect data from a representative sample of 877 participants, i.e. 29,09% of the population of clinical psychologists in South Africa. Statistical analyses were implemented to address a number of key research questions concerning aspects which characterise professional identity, namely: demographic profile; work settings and roles (practices); and theoretical perspective, beliefs and attitudes (values). Findings suggest that, demographically, clinical psychologists do not mirror the clients they serve, and also that there is a large proportion of the population for whom psychological services remain inaccessible and/or inappropriate. Furthermore, the professional identity of clinical psychologists currently does not comprise practices and values which meet the mental health care needs of South Africa. A significant recommendation of the research is its endorsement of the National Health Insurance model given the promise of its role in ensuring psychology remains relevant. It is recommended that future studies expand on these findings qualitatively, and compare clinical psychology with other mental health care fields. Universities are also urged to relook at their training curricula and ensure that trainees are made of aware of issues of policy, and that areas of research and psychological assessment in complex environments are prioritized.
Keywords: Psychologists -- South Africa; Psychology -- Study and teaching (Higher) -- South Africa; Psychology -- Practice -- South Africa